Anti-inflammatory effect of Plantago asiatica crude extract in rat gout arthritis model - Bingjun Qian; Jun Hu; Li Dai; Yue Zhou; Haixia Xu (Journal of Immunotoxicology)
Plantago asiatica L., a perennial herb in the family Plantaginaceae, has been shown to impart several pharmacologic activities, including anti-oxidative, anti-inflammatory, and diuretic effects. In the study here, the anti-gout(y) arthritis (GA) effects of a crude extract from P. asiatica L. (PAE) were investigated in a rat GA model. For this, PAE was prepared by ethanol extraction and analyzed for phytochemicals by RP-HPLC and Q-TOF-MS. Thereafter, potential therapeutic effects of the PAE were investigated in rats; Wistar rats (male, 8 wk-of-age) were randomly allocated into four groups (n = 9/group) and intra-articularly injected with 3 mg monosodium urate (MSU) in saline solution to establish a GA model. For the study, rats received oral dosings of 0.3 mg colchicine/kg or 1 g PAE/kg (w/w) before and after gout was established. At fixed times after the treatments, assessment of joint swelling ratios and pathological changes in the joints, as well as of select cytokine expression in the blood, was done. RP-HPLC results showed the PAE contained at least 8 ‘active’ ingredients, with plantamajoside, verbascoside, and cymaroside being the most abundant. In comparison to in control rats, MSU induced joint space narrowing, ankle joint swelling, and increased levels of pro-inflammatory interleukin (IL)-1β, IL-17a, tumor necrosis factor (TNF)-α, and interferon (IFN)-γ, and reductions in anti-inflammatory IL-10 in the blood. PAE treatment significantly reversed patho- genic joint space narrowing and swelling, reversed the MSU-induced changes in inflammatory factors, and in general imparted effects very similar to those seen with colchicine (COL; known non-steroidal anti-inflammatory drug for clinical treatment of GA). Collectively, these findings provide experimental evidence supporting the potential applicability of PAE to treat gouty arthritis.